Прогностичка вредност нивоа MVCD и MOP1 у серуму у процени прогнозе код пацијената са сепсом: Нивои серума MVCD и MOP1 у прогнози сепсе - Zhan, Xiaobo; Yang, Xue; Zeng, Xiaoqin; Zhou , Quancheng; Cheng, Xiaofan; Liao, Wei (Journal of Medical Biochemistry, 2026)
Objective To investigate the prognostic significance of serum levels of ‌Member of PAS protein 1 (MOP1) and Mammalian-derived Vascular Endothelial Growth Factor (MVCD) for the prognosis of children with sepsis in the pediatric intensive care unit (PICU).Methods We selected 124 pediatric patients with sepsis admitted to our hospital's PICU from September 2023-September 2025 as Group B and another 100 pediatric patients admitted to the PICU during the same period without sepsis-related infections as Group A. Additionally, Pediatric patients with sepsis were split into two groups based on their prognosis after 28 days: a survival group (n = 80) and a mortality group (n = 44). The pediatric patients' levels of MOP1 and MVCD were tested and compared after they were admitted. In pediatric patients with sepsis in the PICU, the predictive significance of serum MVCD and MOP1 was assessed using receiver operating characteristic (ROC) curves. To find out what characteristics affected the prognosis of pediatric sepsis patients in the PICU, multivariate logistic regression analysis was employed.Results Group B's serum levels of MOP1 and MVCD were substantially higher than Group A's. In comparison to the nonsurviving group, the surviving group's serum levels of MVCD and MOP1 were noticeably lower. There were statistically significant differences between the groups (P